The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1111/j.1365-2141.1994.tb06744.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood stem cells (PBSCs) collected after recombinant granulocyte colony stimulating factor (rhG‐CSF): an analysis of factors correlating with the tempo of engraftment after transplantation

Abstract: Factors affecting mobilization and engraftment were analysed in 54 patients undergoing transplant using autologous PBSCs mobilized with high-dose recombinant granulocyte stimulating factor (rhG-CSF). Patients received 5-7 d of rhG-CSF, 16 micrograms/kg/d, administered subcutaneously. PBSCs were harvested by leukapheresis using automated continuous-flow blood cell separators beginning on day 4 of rhG-CSF, processing 10 litres of whole blood, for 2-6 consecutive days. Transplants were performed for the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
225
7
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(247 citation statements)
references
References 14 publications
12
225
7
2
Order By: Relevance
“…Most of the patients did not require RBC transfusion and patients treated with growth factors after PBPCT had a less marked decline of Hb levels than patients treated with PBPCT only (Figure 1). The administration of EPO with G-CSF and GM-CSF after PBPCT probably abrogated the previously described detrimental effect of G-CSF and GM-CSF on PLT recovery after PBPCT (Spitzer et al, 1994;Shimazaki et al, 1994;Bensinger et al, 1994), which could be caused by a prevalent potentiation of myelopoiesis with a consensual progenitor cell competition in vivo. Patients treated with growth factors did not require systemic antibiotic therapy with the total abrogation of neutropenic fever in G-CSF plus EPO-treated patients, while GM-CSF plus EPO-treated patients experienced only episodes of intermittent hyperthermia, which did not meet the criteria for the start of systemic antibiotic treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Most of the patients did not require RBC transfusion and patients treated with growth factors after PBPCT had a less marked decline of Hb levels than patients treated with PBPCT only (Figure 1). The administration of EPO with G-CSF and GM-CSF after PBPCT probably abrogated the previously described detrimental effect of G-CSF and GM-CSF on PLT recovery after PBPCT (Spitzer et al, 1994;Shimazaki et al, 1994;Bensinger et al, 1994), which could be caused by a prevalent potentiation of myelopoiesis with a consensual progenitor cell competition in vivo. Patients treated with growth factors did not require systemic antibiotic therapy with the total abrogation of neutropenic fever in G-CSF plus EPO-treated patients, while GM-CSF plus EPO-treated patients experienced only episodes of intermittent hyperthermia, which did not meet the criteria for the start of systemic antibiotic treatment.…”
Section: Discussionmentioning
confidence: 88%
“…[7][8][9] As for platelet recovery, few studies have been reported; some have shown that the number of CFU-GM and CD34 + cells correlate with platelet recovery, 7-14 but others have not shown a significant correlation. 15,16 Recently, specific markers for megakaryocyte progenitors such as colony-forming unit megakaryocyte (CFU-MK) and CD34 + /CD41 + or CD34 + /CD61 + cells have predicted platelet engraftment in PBSCT.…”
mentioning
confidence: 99%
“…more than 2.5 x 106 CD34+ cells kg-' were collected for most control patients), and the loss of cells during the separation procedure. It is interesting that the number of CD34+ cells that were infused in patients in the study group was below the threshold that we (Faucher et al, 1996) and others (Bender et al 1992;Bensinger et al, 1994: Haas et al, 1994Weaver et al 1995) considered as the minimal number necessary to ensure the quickest haematological recovery with unselected PBSCs; on the other hand, patients in the control group received on average a number of CD34+ cells that was close to or above this threshold. The loss of progenitor cells may explain the delay in platelet recovery observed after transplantation of autologous marrow CD34+ cells, which was previously demonstrated (Shpall et al, 1997).…”
Section: Patient Characteristics and Blood Cell Mobilizationmentioning
confidence: 67%
“…regarding the minimal number of CD34+ cells that ensures optimal engrafment (Bender et al, 1992;Bensinger et al 1994: Haas et al 1994van de Wall et al, 1994;Faucher et al 1996). and on the assumption that the yield of the cell separation procedure would be approximately 50%, thus providing for similar numbers of progenitors in both groups.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation